Pelaksanaan Perkawinan Adat Asli Masyarakat Melayu antara Bergelar Raja dengan tidak Bergelar Raja - Rhezky Putra Dinata; Desi Apriani; Lidia Febrianti; Esy Kurniasih; Umi Muslikhah; Heni Susanti (Jurusan Sejarah, Seni, dan Arkeologi, FKIP, Universitas Jambi, 2021)
Abstract: Customary law is an unwritten law that is recognized in the 1945 Constitution. One of the indigenous peoples in Indonesia who still practice their customary law is the indigenous Malay community, especially in the city of Pekanbaru. The law of marriage for the Malay customary community must be carried out in stages and irrationally in accordance with the stages of the implementation of marriage and Malay teachings with Islamic nuances, especially in marriages between people with the title of King and people who do not have the title of King that occur among the Malay community which will also affect the children, assets, and the position of husband and wife. The main problem in this research is how the implementation of traditional Malay marriages between those with the title of King and those who do not have the title of King in Pekanbaru, and what are the legal consequences for the occurrence of marriages between those with the title of King and those who do not have the title of King for children, assets, and the position of husband and wife in the indigenous Malay community in Pekanbaru.The method used in this study when viewed from its kind is using observational research methods using survey methods. From the results of the research it is known that currently there are still many children from parents from among people with titles of Kings or nobles in Pekanbaru who carry out marriage customs, but many of these traditional marriage processions have been abandoned and keep up with the times which of course are no longer appropriate. with the authenticity of the marriage customs of the Malay community. Keywords: Marriage, Custom, Original, Titled King. Abstrak: Hukum adat merupakan hukum tidak tertulis yang diakui dalam Undang-undang Dasar 1945. Salah satu masyarakat adat di Indonesia yang masih menjalankan hukum adatnya adalah masyarakat adat Melayu terkhususnya di Kota Pekanbaru. Hukum nikah kawin bagi masyarakat adat Melayu harus dilaksanakan secara bertahap dan irasional sesuai dengan tahapan pelaksanan kawin kawin dan tunjuk ajar Melayu yang bernuansa Islam, terutama dalam perkawinan antara orang bergelar Raja dengan orang yang tidak bergelar Raja yang terjadi dikalangan masyarakat Melayu yang juga akan berpengaruh pada anak, harta, dan kedudukan suami istri.Permasalahan pokok dalam penelitian ini ialah bagaimana pelaksanaan perkawinan adat asli masyarakat Melayu antara bergelar Raja dengan tidak bergelar Raja di Pekanbaru, serta bagaimana akibat hukum terhadap terjadinya perkawinan antara yang bergelar Raja dengan tidak bergelar Raja terhadap anak, harta, dan kedudukan suami istri pada masyarakat adat asli Melayu di Pekanbaru.Metode yang digunakan dalam penelitian ini jika dilihat dari jenisnya yaitu menggunakan metode observasional researchdengan menggunakan cara survey. Dari hasil penelitian diketahui bahwa saat ini masih banyak anak dari para orangtua dari kalangan orang bergelar Raja atau bangsawan di Pekanbaru yang melangsungkan adat nikah kawin namun beberapa dari prosesi adat nikah kawin tersebut sudah banyak yang ditinggalkan dan mengkuti perkembangan zaman yang tentu saja sudah tidak sesuai lagi dengan keaslian adat nikah kawin masyarakat Melayu. Kata kunci :Perkawinan, Adat, Asli, Bergelar Raja